Trace Metal Dynamics in a Tropical Mangrove Tidal Creek: Influence of Porewater Seepage (Can Gio, Vietnam) - Thanh-Nho, Nguyen; Marchand, Cyril; Strady, Emilie; Van Vinh, Truong; Taillardat, Pierre; Cong-Hau, Nguyen; Nhu-Trang, Tran-Thi (Frontiers in Environmental Science, 2020)
Mangrove soils are considered as sinks for trace metals, protecting coastal waters from pollutions. However, the cycling of trace metals in mangroves is complex due to various biogeochemical processes across the intertidal zone, notably the dissolution of bearing phases resulting in high trace metal concentrations in porewaters. Previous studies demonstrated a decrease of trace metal stocks in mangrove soils seaward, possibly due to the export of dissolved metals through tidal pumping. Can Gio mangrove is the largest one in Vietnam, developing downstream Ho Chi Minh City (Viet Nam’s biggest industrial city). The objectives of the present study were to characterize the dynamics of trace metals in a tidal creek of the Can Gio mangrove that does not receive any upstream inputs and to identify the role of porewater seepage on their dynamics. To reach our goals, surface water and suspended particulate matters were collected every 2 h during two different tidal cycles (spring and neap tides) and at the two different seasons, dry and wet. Mangroves porewaters were also collected. In addition to particulate and dissolved trace metals, physico-chemical parameters and a groundwater tracer (Radon – 222Rn) were measured. The results showed that trace metal concentrations at flood tides, both in the dissolved and the particulate phases, were in the same range that those measured in the Can Gio Estuary. Then during ebb tides, we evidenced high inputs of dissolved Fe, Mn, Co, and Ni from mangrove soils. However, the dynamics of these inputs differed depending on the element considered. Mn was exported from the tidal creek in its dissolved form. However concerning Fe, and to a lesser extent Co and Ni, we suggest that, when delivered to the creek from the soils under dissolved forms, these trace metals precipitated because of different physicochemical characteristics between mangrove soils and tidal creek, notably higher dissolved oxygen concentrations and higher pH. Consequently, these elements were exported to the estuary in particulate forms. We suggest that budget studies of trace metals in mangroves should be developed like the ones concerning carbon to efficiently determine their role as a barrier for pollutants between land and sea.